2022
DOI: 10.3389/fpsyg.2022.952503
|View full text |Cite
|
Sign up to set email alerts
|

English as a foreign language teachers’ professional success in the Chinese context: The effects of well-being and emotion regulation

Abstract: Given the significance of teachers’ professional success in the adequacy of education, exploring the determinants of this variable appears crucial. To address this need, this inquiry inspected the role of well-being and emotion regulation in Chinese EFL teachers’ professional success. For this purpose, 357 Chinese EFL teachers were selected to answer three pre-designed questionnaires. Structural equation modeling (SEM) using Smart-PLS was implemented to analyze teacher participants’ responses. The structural m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 63 publications
(72 reference statements)
2
25
0
Order By: Relevance
“…A part of the findings evidenced that a strong correlation existed between the EFL university professors’ ER and their self-efficacy. These findings lend support to the results of the previous studies disclosing that there was the intertwined relationship between teachers’ ER and their self-efficacy (Burić et al, 2017 ; Burić et al, 2020 ; Burić & Macuka, 2017 ; Chen & Cheng, 2021 ; Fan & Wang, 2022 ). Similarly, Burić and Moè ( 2020 ) found interrelationships of teachers’ self-efficacy, pleasant emotions, and well-being, which, in turn, affect their enthusiasm.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A part of the findings evidenced that a strong correlation existed between the EFL university professors’ ER and their self-efficacy. These findings lend support to the results of the previous studies disclosing that there was the intertwined relationship between teachers’ ER and their self-efficacy (Burić et al, 2017 ; Burić et al, 2020 ; Burić & Macuka, 2017 ; Chen & Cheng, 2021 ; Fan & Wang, 2022 ). Similarly, Burić and Moè ( 2020 ) found interrelationships of teachers’ self-efficacy, pleasant emotions, and well-being, which, in turn, affect their enthusiasm.…”
Section: Discussionsupporting
confidence: 88%
“…Given that effective educational systems are made by successful teachers, factors contributing to their professional success should be carefully studied. To give an appropriate response to this necessity, different factors, such as personal factors (Derakhshan et al, 2020 ; Fathi et al, 2021a , b ), interpersonal factors (Nayernia et al, 2020 ; Pishghadam et al, 2021 ), and emotional factors (Fan & Wang, 2022 ; Namaziandost et al, 2022 ) should be studied. Previous research has shown that there is a mutual relationship between teachers’ professional success and well-being (Fan & Wang, 2022 ; Wong & Zhang, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the adjustment of the associations between expectancy-value motivation and learning consequences requires the identification of the origins of expectancy and value that can be changed. It should be noted that motivation is considered a changeable, collaborative construct ( Dörnyei et al, 2015 ; Fan and Wang, 2022 ), so curriculum designers, teachers, policy-makers, and researchers can bridge the achievement gaps, driving more learners to make sustained efforts in academic situations, both in the short and long term.…”
Section: Pedagogical Implications and Suggestions For Further Researchmentioning
confidence: 99%
“…Others notice emotions through non-verbal clues including facial expression gestures, vocalics and body language (Mehrabian and Epstein, 1972). Nevertheless, sometimes these emotions are recognized incorrectly (Gregersen et al, 2017;Elahi Shirvan and Talezadeh, 2018;Fan and Wang, 2022). Therefore, it is essential to look for insightful information about the underlying mechanisms of emotion contagion in the foreign language learning context, now that we acknowledge the truth of this event.…”
Section: The Procedures Of Emotion Contagionmentioning
confidence: 99%